Pemberdayaan Guru Sekolah Dasar Negeri Arjosari Kabupaten Pacitan - Kurdi, Imam, Prof. Dr. Sutama, M.Pd, Dr. Sofyan Anif, M.Si (2014)
To realize that schools have the advantage of quality academic and nonacademic leadership strategies necessary for principals in managing human resources. Teachers as a leading fighter in the learning process should be more efficient, competent, and eager to achieve national education goals. This study aims to: (1) Describing the provision of teacher recruitment SDN Arjosari, (2) Describe the training and development of teachers SDN Arjosari, (3 ) Describe the teacher control in SDN Arjosari. This study is a qualitative study using an ethnographic approach. Place of execution of this study is on the SDN Arjosari Pacitan. Interviewees in this study include principals, teachers, chairman of the committee, and the school superintendent. Collecting data using observations, interviews and documentation. The validity of the data was tested by using triangulation. Then for data analysis techniques using version Milles and Huberman, by way of data reduction, data and drawing conclusions and verification. The results ofthe study showed that theprincipalof SDN Arjosari, Pacitan in teacher empowerment in principle to carry out the task and role to the fullest in managing human resources at his school. Form of empowerment include teacher recruitment, training and development of teachers, and teacher control. Of the three sub focus could be demonstrated that: (1) On recruitment of teachers, that teacher to meet the needs of both qualitative and quantitative implemented two phases: planning and execution. Planning activities include, (a) a description of the work that needs to be filled. (B) the analysis of work, work to be done. (C) specification of the work that teacher candidates will be accepted, (d) the requirements of the job. Then begins the implementation phase of the announcement, withdrawal, selection, placement, orientation to work. (2) On the promotion and development includes three aspects, namely, increasing the professionalism of coaching, career coaching, and coaching welfare. Coaching increased professionalism and training activities carried out by non-training and empowerment Teacher Working Group (KKG). (3) Than on the teacher controls implemented to regulate, restrain, supervise and directthe expense of their duties and responsibilities. In addition,the control ofthe teacherintended to evaluate teacher performance, aiming to assess the repair, improvement or correction objective if there is a discrepancy or deviation duties, powers and responsibilities that exist.